2021
DOI: 10.3390/antibiotics10010049
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive “Smart” Hydrogel for Controlled Delivery of Silver Nanoparticles to Infected Wounds

Abstract: Persistent wound infections have been a therapeutic challenge for a long time. Current treatment approaches are mostly based on the delivery of antibiotics, but these are not effective for all infections. Here, we report the development of a sensitive pH-responsive hydrogel that can provide controlled, pH-triggered release of silver nanoparticles (AgNPs). This delivery system was designed to sense the environmental pH and trigger the release of AgNPs when the pH changes from acidic to alkaline, as occurs due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 37 publications
(45 reference statements)
3
74
0
Order By: Relevance
“…Collagen in the form of hydrogel is suitable for various applications, including biomedical and tissue engineering, as it can absorb water molecules or swell when in contact with aqueous solutions due to the presence of hydrophilic groups in its backbone [47,48]. This would enable the diffusion of oxygen, proteins, and growth factors that are important in drug delivery, cell encapsulation, wound dressing, and tissue repair [47,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen in the form of hydrogel is suitable for various applications, including biomedical and tissue engineering, as it can absorb water molecules or swell when in contact with aqueous solutions due to the presence of hydrophilic groups in its backbone [47,48]. This would enable the diffusion of oxygen, proteins, and growth factors that are important in drug delivery, cell encapsulation, wound dressing, and tissue repair [47,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Cells treated with fresh DMEM were used as controls. After further incubation for 24 h, the cells were washed and resazurin dye was added and fluorescence intensity was measured after 2 h incubation at 37 • C. Cells that were grown and treated in glass coverslips were stained with Live/Dead staining according to the manufacturers' instructions, similar to our previous method [20]. Samples were imaged via Olympus IX81 epifluorescence microscope (Olympus, Tokyo, Japan).…”
Section: In Vitro Cytocompatibilitymentioning
confidence: 99%
“…The controlled release of Ag + from a hydrogel is another important aspect, as studies have shown that AgNPs have a short lifetime (3 h) while the inconsistent and fast release of Ag + contributes to high wound toxicity [ 18 ]. Consequently, the controlled release mechanism of AgNPs has been integrated with different delivery platforms i.e., antibacterial coatings [ 19 ], stimuli-responsive hydrogel to provide on-demand release [ 20 ], mussel-inspired hydrogels [ 21 ], and mesoporous silica nanoparticles with the slow dissolution of Ag + [ 22 ], many of which show promising in-vitro results. While their antibacterial activity is relatively well studied using in-vitro models, the AgNPs’ efficacy against mature biofilms in clinically relevant animal models is unconvincingly reported.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study highlighted the potential of silver NPs loaded in pH responsive hydrogels as a potential candidate for wound healing. This was due to the unique property of switching to a hydrated state in the alkaline wound environment, resulting in the sustained release of silver NPs with antibacterial properties [65]. Another study assessing the efficacy of gold nanorods released from different hydrogels namely polyethylene glycol (PEG) and cationic poly allyl amine hydrochloride (PAH) demonstrated prominent wound healing ability with complete closure of the wound within 14 days of the treatment along with improved skin re-epithelialization and collagen formation as well as noticeable impact on the inflammatory gene expression [79].…”
Section: Wound Healingmentioning
confidence: 99%